THE IMPACT OF TOURISM ACTIVITIES ON THE ENVIRONMENT OF MOUNT KINABALU, UNESCO WORLD HERITAGE SITE - Abdul Latip, Normah; Jaafar, Mastura; Marzuki, Azizan; Roufechaei, Kamand Mohammadzadeh; Umar, Mohd Umzarulazijo; Karim, Rehmat (PLANNING MALAYSIA, 2020)
Tourism contributes to the conservation and protection of mountainous areas, and even the characteristics and activities of tourism also affect the environmental sustainability of an area. This study aims to identify tourist characteristics, their opinion towards a sustainable environment, their activities conducted at the park and environmental impacts. Overall, 383 respondents agreed to participate, and the response has been analysed using the relative importance’s of these activities, and environmental impacts were quantified by the relative importance index method. Most of them visited Mount Kinabalu to experience natural sightseeing and hiking activity. Majority of them know environmental concern but feeling that KNP is rather crowded. Overall, the most popular activities were mount climbing and wildlife sightseeing by domestic and international tourist. The result of the study also has shown that noise and air pollution were ranked as the most important environmental impacts factors. Considering mountain tourism is an attraction and contributor to the economy of Sabah, there must be effective preventive measures. Because of that, planning, implementing and strengthening new policies and rules for tourist activities regarding the conservation and protection will help to minimize the impacts of tourism. Through the results of the study using the Relative Importance Index (RII) analysis, it is hoped that it will be able to help provide suggestions and solutions to balance the impacts of tourism in Mount Kinabalu towards sustainability.